2023
DOI: 10.1016/j.jcjo.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of choroidal changes following COVID-19 infection: analysis of choroidal thickness and choroidal vascularity index

Abstract: Purpose The aim of this study was to investigate subclinical choroidal involvement in patients with systemic COVID-19 infection and evaluate its long-term course. Materials and Methods This prospective, longitudinal study included 32 eyes of 16 COVID-19 patients and 34 eyes of 17 age-matched healthy control subjects. All of the participants had a detailed ophthalmological including visual acuity assessment, slit lamp examination and indirect ophthalmoscopy. Enhanced dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Firat et al reported that the choroidal thickness of patients with a relatively mild course who had COVID-19 but were not hospitalized, and no significant difference was found in the choroidal thickness compared to the control group 49 . In the study of Hepokur et al, choroidal thickness was found to decrease in COVID-19 during the early post-infectious period and to normalize during the late post-infectious period 50 . However, this study was performed in the early period of the COVID-19 pandemic and there is no anticoagulant treatment in the treatment protocol.…”
Section: Discussionmentioning
confidence: 92%
“…Firat et al reported that the choroidal thickness of patients with a relatively mild course who had COVID-19 but were not hospitalized, and no significant difference was found in the choroidal thickness compared to the control group 49 . In the study of Hepokur et al, choroidal thickness was found to decrease in COVID-19 during the early post-infectious period and to normalize during the late post-infectious period 50 . However, this study was performed in the early period of the COVID-19 pandemic and there is no anticoagulant treatment in the treatment protocol.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, choroidal thickness was found to be significantly lower at all measurement points in both groups with COVID-19 when compared to the control group. Choroidal thickness and total choroidal area have been found to be significantly lower in the early postinfectious period in COVID-19 patients compared to healthy individuals in the literature [ 9 , 10 ].In contrast, the study where patients with mild COVID-19 infection were compared to a healthy control group found no significant difference in terms of choroidal thickness and CMT [11] . We think that the difference in the duration between the COVID-19 infection diagnosis and the ophthalmology examination in this study (14 to 60 days) and the differences in inflammatory cytokine density may have caused this contrasting result.…”
Section: Discussionmentioning
confidence: 99%
“…We think that the difference in the duration between the COVID-19 infection diagnosis and the ophthalmology examination in this study (14 to 60 days) and the differences in inflammatory cytokine density may have caused this contrasting result. On the other hand, studies exist on the early and late stage effects of COVID-19 infection on the ocular vascular structures [ 10 , 17 ] but whether these changes are permanent is not known. The included patients in our study were within the 3-month period folowing the COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous OCT angiography study, Turker et al found an increase in choriocapillaris flow along with a decrease in vascular flow in the retinal capillary plexuses in Covid-19 patients [ 16 ]. Another study evaluated early and late choroidal thickness and choroidal vascularity index in Covid-19 patients and found that the choroidal changes detected in the early period resolved at the nine months postinfectious period [ 17 ]. Abdelmassih et al evaluated OCT images in Covid-19 patients and obtained findings in favor of choroidopathy in indocyanine green (ICG) angiography as well as choroidal thickening [ 8 ].…”
Section: Discussionmentioning
confidence: 99%